2007
DOI: 10.1080/15226510601139409
|View full text |Cite
|
Sign up to set email alerts
|

Phytovolatilization of Oxygenated Gasoline-Impacted Groundwater at an Underground Storage Tank Site Via Conifers

Abstract: A stand of five conifers (Pinus sp.) bordering a gasoline service station was studied to estimate the methyl tert-butyl ether (MTBE) emission rate from gasoline-impacted groundwater. Groundwater was impacted with gasoline oxygenates MTBE and tert-butyl alcohol (TBA) at combined concentrations exceeding 200,000 microg/L. Condensate from trees was collected in sealed environmental chambers and analyzed. Concentrations of MTBE in condensate ranged from 0.51 to 460 microg/L; TBA ranged from 12 to 4100 microg/L (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The trees were located in a flood plain of the Savannah River, between South Carolina and Georgia, that received contaminated groundwater discharge. This detection of MTBE in trees at the field scale was later confirmed to occur in coniferous evergreens by Arnold et al (2007). This detection of MTBE in trees at the field scale was later confirmed to occur in coniferous evergreens by Arnold et al (2007).…”
Section: Plant Tissue Samplesmentioning
confidence: 71%
See 2 more Smart Citations
“…The trees were located in a flood plain of the Savannah River, between South Carolina and Georgia, that received contaminated groundwater discharge. This detection of MTBE in trees at the field scale was later confirmed to occur in coniferous evergreens by Arnold et al (2007). This detection of MTBE in trees at the field scale was later confirmed to occur in coniferous evergreens by Arnold et al (2007).…”
Section: Plant Tissue Samplesmentioning
confidence: 71%
“…Arnold et al (2007) investigated MTBE loss by existing vegetation at a gasoline site in California characterized by MTBE-and TBA-contaminated groundwater. Arnold et al (2007) investigated MTBE loss by existing vegetation at a gasoline site in California characterized by MTBE-and TBA-contaminated groundwater.…”
Section: Plant Interaction and Uptake Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, anaerobic conditions do not often result in high biodegradation rates, and increased oxygen supply may be required to enhance the process [80][81][82]. Phytoremediation studies have shown that various plant species, such as poplars [83,84], alfalfa [85], weeping willows [86], or conifers [87], remove MTBE from groundwater through their roots, but no evidence has been provided that MTBE is degraded within plant tissue [84][85][86][87][88][89]; rather, it is transpired, resulting in potentially harmful emissions. However, no plant toxicity effects have been reported [86].…”
Section: Fate Of Mtbe In Constructed Wetlandsmentioning
confidence: 99%
“…Peer‐reviewed studies have reported the successful use of phytoremediation tree systems to hydraulically contain and mitigate petroleum hydrocarbon contamination in the subsurface (Arnold et al., ; Barac et al., ; El‐Gendy et al., ; Ferro et al., , ; Hong et al., ; Landmeyer, ). Groundwater phytoremediation systems best decrease contaminant mass for more soluble analytes of petroleum hydrocarbons such as benzene, ethylbenzene, toluene, and xylenes (BTEX; Barac et al., ; El‐Gendy et al., ; Ferro et al, , ; Landmeyer, ) and fuel oxygenates such as methyl ‐tert ‐butyl ether (MTBE; Arnold et al., ; Hong et al., ). Most of the aforementioned studies have been implemented at sites with shallow, contaminated groundwater where depth to groundwater is less than 3 m. A few studies have used trees to reach greater groundwater depths at 4 m to 5 m below ground surface (Barac et al., ; Ferro et al., ) for hydraulic‐containment and mass reduction of mixed gasoline and diesel fuels.…”
Section: Introductionmentioning
confidence: 99%